Congenital bilateral syngnathia and tracheoesophageal fistula: A rare presentation - Ankit Khasgiwala; Sagar Jangam; Shashi Sharma; Vilas Newaskar (Wolters Kluwer Medknow Publications, 2016)
Congenital syngnathia (CS), first reported by Burket in 1936, is a rare condition, with <50 reported cases and is associated with other conditions and syndromes. CS restricts mouth opening, causing difficulty in feeding, swallowing, and respiration. This report puts forth the clinical findings and management of this challenging condition in association with tracheoesophageal fistula in a neonate.